Nanofiber based drug delivery systems for skin: A promising therapeutic approach - Kamble, Pallavi; Sadarani, Bhakti; Majumdar, Anuradha; Bhullar, Sukhwinder Kaur (Elsevier, 2017)
Delivery of drugs through the skin has evolved from the crude application on to the wound or site of infection to more compact drug delivery systems. Recently, the focus of drug delivery through the skin has been attaining higher precision and accuracy to the site of action than earlier conventional methods. Skin delivery does not only involve drug application in disease condition but also encompasses drug delivery to improve the skin quality. Decreasing the size of drug carriers has emerged as a thumb rule for better permeability through crooked pathways in the skin. Nanofiber mats offer distinct operational advantages such as high porosity as well as high specific surface areas. This review elaborates the advancements in the nanofiber-based mats in drug delivery for pharmaceutical and cosmetic use. (C) 2017 Elsevier B.V. All rights reserved.
Keywords: Cosmetic use; Nanofiber; Skin delivery; Transdermal; Wound healing